Kontrak Elektronik dalam Mekanisme Hukum di Indonesia - Kusuma Wardani, Ikhlasul Sholah; Safirah, Alya; Qurrotulaini, Alfika Salsa (LPPM Universitas Ekasakti Padang, 2024)
The development of technology changes the way humans carry out activities to meet their daily needs. In this context, carrying out legal actions in the field of agreements, in this case, electronic contracts (sale and purchase, rental, etc.). This act is of course framed by law, electronic contracts are facilitated by the UU ITE. Of course, legal subjects question the concrete form of electronic contracts referred to in the UU ITE. The research method in this scientific writing is legal research, which uses legal materials such as laws, jurisprudence and legal norms. In simple terms, an electronic contract is a legal act carried out by people in an online network or electronic system, for example in buying and selling via e-commerce (Tokopedia, Shopee, et al) or when people use electronic-based transportation services (Gojek, Grab, et al), or when the public participates in the auction process via an electronic system (lelang.go.id).